2008
DOI: 10.1093/carcin/bgn156
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic cyclooxygenase-2 expression and high salt enhanced susceptibility to chemical-induced gastric cancer development in mice

Abstract: Cyclooxoygenase (COX)-2 overexpression is involved in gastric carcinogenesis. While high-salt intake is a known risk factor for gastric cancer development, we determined the effects of high salt on gastric chemical carcinogenesis in COX-2 transgenic (TG) mice. COX-2 TG mice were developed in C57/BL6 strain using the full-length human cox-2 complementary DNA construct. Six-week-old COX-2 TG and wild-type (WT) littermates were randomly allocated to receive alternate week of N-methyl-N-nitrosourea (MNU, 240 p.p.m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…As indicated earlier, normal gastric epithelial cells do not express Runx3 [12,22,26] and it has been reported that MNUinduced gastric tumors in mice are associated with chronic infiltration of inflammatory cells and that inflammation promotes MNU-induced gastric tumors [107]. Moreover, it has been shown that gastric cancer development in mice transgenic for Wnt1, Ptgs2 and Ptges (Gan mice) is dependent on TNFα and tumor formation could be rescued in TNFα −/− mice by transfer of bone marrow-derived DCs from TNFα +/+ mice, which infiltrated the tumors [108].…”
Section: Git Tumorsmentioning
confidence: 74%
“…As indicated earlier, normal gastric epithelial cells do not express Runx3 [12,22,26] and it has been reported that MNUinduced gastric tumors in mice are associated with chronic infiltration of inflammatory cells and that inflammation promotes MNU-induced gastric tumors [107]. Moreover, it has been shown that gastric cancer development in mice transgenic for Wnt1, Ptgs2 and Ptges (Gan mice) is dependent on TNFα and tumor formation could be rescued in TNFα −/− mice by transfer of bone marrow-derived DCs from TNFα +/+ mice, which infiltrated the tumors [108].…”
Section: Git Tumorsmentioning
confidence: 74%
“…In a different approach, wild-type or COX-2 transgenic mice were treated with MNU. Whereas COX-2 overexpression alone did not lead to tumor development, the tumor incidence after MNU treatment was almost double in the COX-2 transgenic mice, suggesting a role of tumor promotion for COX-2 [91]. Also, gastric tumor multiplicity was higher in K19-C2mE mice that were treated with MNU and H. pylori compared to treated wild-type mice [92].…”
Section: In Vivo Modelsmentioning
confidence: 88%
“…To this end, we have previously conducted extensive research and discovered an array of molecular regulators associated with stomach cancer development. [13][14][15][23][24][25] In particular, we recently demonstrated a causal relationship between H. pylori infection and aberrant DNA methylation in the host genome by cross-species epigenomics analysis, and revealed that epigenetic silencing of the antitumorigenic transcriptional regulator FOXD3 is a major mechanism responsible for the H. pylori-induced gastric carcinogenesis. 16,17 Here we provide new evidence that GDF1, which functions to protect gastric epithelial cells against malignant transformation by upholding SMAD signaling (Figures 3 and 4), is also susceptible to epigenetic silencing in the majority of mouse and human gastric cancers (Figures 1, 2 and 5).…”
Section: Discussionmentioning
confidence: 99%